The relationship of mother’s feeding practices and the frequency of diarrhoea in under-five children - Rachmawati, Praba Dlyan; Wahyuni, Ema Dwi; Syaifan Muhsin, Miftahul Desiyan; Klankhajhon, Sirikanok (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the relationship between a mother’s feeding practice and the incidence of diarrhoea in children aged <5. Method: The quantitative, descriptive-analytical, cross-sectional study was conducted in June 2021, in Tropodo village, Waru district, Sidoarjo, Indonesia, and comprised mothers having children who were aged <5 years. Mother’s feeding practice was the independent variable, while the dependent variable was the incidence of diarrhoea in children. Data was collected using the Comprehensive Feeding Practices Questionnaire and the relevant portions of the Demographic and Health Survey questionnaire. Data was analysed using Spearman Rho test. Results: Of the 217 mothers, 110(50.7%) were aged 30-40 years, and of the 217 children, 96(44.2%) were aged 1 year. There were 124(57.1%) girls and 93(42.9%) boys among the children. There was a significant relationship between mother’s feeding practice and the incidence of diarrhoea in children <5 (p=0.004; r=0.194). Conclusion: Inappropriate maternal feeding practices were found to have the potential to cause diarrhoea in children aged <5. Keywords: Feeding, Diarrhoea, Children.